The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/der.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing for Metal Allergy With Manufacturer-Supplied Materials Before Nuss Bar Insertion

Abstract: The metal disc may not be adequately sensitive to determine nickel allergy before the Nuss procedure. Patch testing alone with standard formulations of nickel sulfate in petrolatum may be more sensitive in diagnosing nickel allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The previous method was found not to be adequately sensitive in preoperative screening (specifically looking for nickel allergy). It was found that patch tests using metal in petrolatum was a more sensitive and accurate means of preoperative nickel allergy testing [12]. Hypersensitivity to the skin test manifests most often within 48-96 h from exposure, but in some cases it may take up to 168 h. The results of preoperative testing may be influenced by drugs, other allergens, active neoplastic disease, age, or inborn histamine intolerance [12,13].…”
Section: Mechanismmentioning
confidence: 99%
“…The previous method was found not to be adequately sensitive in preoperative screening (specifically looking for nickel allergy). It was found that patch tests using metal in petrolatum was a more sensitive and accurate means of preoperative nickel allergy testing [12]. Hypersensitivity to the skin test manifests most often within 48-96 h from exposure, but in some cases it may take up to 168 h. The results of preoperative testing may be influenced by drugs, other allergens, active neoplastic disease, age, or inborn histamine intolerance [12,13].…”
Section: Mechanismmentioning
confidence: 99%
“…The positive skin test to the disc and the resolution of signs and symptoms after removal suggest that the titanium allergy was relevant to the patient's favorable outcome. Testing with metal discs has been discouraged because of concerns about false negative patch testing (22). Despite these concerns, this patient exhibited a type IV hypersensitivity reaction to the disc, which was the basis for implant removal.…”
Section: Casementioning
confidence: 99%
“…Implant failure in Nuss patients is much less likely due to the short amount of time they are left implanted (minimum of two years) [23]. It has been estimated that metal allergy in Nuss patients may have an incidence of about 2.2%, with some evidence of this being up to 6.4% [14,23-24]. A study examining the metal disc offered by the Nuss bar manufacturer for preoperative metal allergy evaluation of pectus excavatum patients found that it was not adequately sensitive in preoperative screening (specifically looking for nickel allergy).…”
Section: Reviewmentioning
confidence: 99%
“…A study examining the metal disc offered by the Nuss bar manufacturer for preoperative metal allergy evaluation of pectus excavatum patients found that it was not adequately sensitive in preoperative screening (specifically looking for nickel allergy). However, it was found that PT using metal in petrolatum was a more sensitive and accurate means of preoperative nickel allergy testing [24]. Due to the morbidity of allergic reactions in patients undergoing Nuss procedure as well as a means of potentially avoiding revision surgery, it has been suggested that PT be used on all patients prior to the Nuss procedure [23-24].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation